Ribosomal Biogenesis and Translational Flux Inhibition by the Selective Inhibitor of Nuclear Export (SINE) XPO1 Antagonist KPT-185 - Tabe, Yoko; Kojima, Kensuke; Yamamoto, Shinichi; Sekihara, Kazumasa; Matsushita, Hiromichi; Davis, Richard Eric; Wang, Zhiqiang; Ma, Wencai; Ishizawa, Jo; Kazuno, Saiko; Kauffman, Michael; Shacham, Sharon; et al. (PLOS ONE, 2015)
Mantle cell lymphoma (MCL) is an aggressive B-cell lymphoma characterized by the aberrant expression of several growth-regulating, oncogenic effectors. Exportin 1 (XPO1) mediates the nucleocytoplasmic transport of numerous molecules including oncogenic growth-regulating factors, RNAs, and ribosomal subunits. In MCL cells, the small molecule KPT-185 blocks XPO1 function and exerts anti-proliferative effects. In this study, we investigated the molecular mechanisms of this putative anti-tumor effect on MCL cells using cell growth/viability assays, immunoblotting, gene expression analysis, and absolute quantification proteomics. KPT-185 exhibited a p53-independent anti-lymphoma effect on MCL cells, by suppression of oncogenic mediators (e.g., XPO1, cyclin D1, c-Myc, PIM1, and Bcl-2 family members), repression of ribosomal biogenesis, and downregulation of translation/chaperone proteins (e.g., PIM2, EEF1A1, EEF2, and HSP70) that are part of the translational/transcriptional network regulated by heat shock factor 1. These results elucidate a novel mechanism in which ribosomal biogenesis appears to be a key component through which XPO1 contributes to tumor cell survival. Thus, we propose that the blockade of XPO1 could be a promising, novel strategy for the treatment of MCL and other malignancies overexpressing XPO1.